Autistic traits in treatment-seeking transgender adults - Nobili, Anna; Glazebrook, Cris; Bouman, Walter Pierre; Glidden, Derek; Baron-Cohen, Simon; Allison, Carrie; Smith, Paula; Arcelus, Jon (Springer, 2018)
The present study aimed to compare prevalence of autistic traits as measured by the Autism Spectrum Quotient-Short (AQ-Short) in a transgender clinical population (n=656) matched by age and sex assigned at birth to a typical cisgender community sample. Transgender people assigned female at birth were approximately twice as likely to have clinically significant levels of autistic traits compared to cisgender females. No difference was found between those assigned male at birth. High level of AQ scores may not be indicative of the presence of an autism spectrum condition as the difference between groups mainly related to social difficulties. Such AQ scores may be a reflection of transgender people presenting with high levels of social anxiety due to negative past experiences.